Modelling relationships between match events and match outcome in elite football - Liu, H.; Hopkins, W. G.; Gomez, M.-A. (European Journal of Sport Science, 2016)
Identifying match events that are related to match outcome is an important task in football match analysis. Here we have used generalised mixed linear modelling to determine relationships of 16 football match events and 1 contextual variable (game location: home/away) with the match outcome. Statistics of 320 close matches (goal difference = 2) of season 2012-2013 in the Spanish First Division Professional Football League were analysed. Relationships were evaluated with magnitude-based inferences and were expressed as extra matches won or lost per 10 close matches for an increase of two within-team or between-team standard deviations (SD) of the match event (representing effects of changes in team values from match to match and of differences between average team values, respectively). There was a moderate positive within-team effect from shots on target (3.4 extra wins per 10 matches; 99% confidence limits ±1.0), and a small positive within-team effect from total shots (1.7 extra wins; ±1.0). Effects of most other match events were related to ball possession, which had a small negative within-team effect (1.2 extra losses; ±1.0) but a small positive between-team effect (1.7 extra wins; ±1.4). Game location showed a small positive within-team effect (1.9 extra wins; ±0.9). In analyses of nine combinations of team and opposition end-of-season rank (classified as high, medium, low), almost all between-team effects were unclear, while within-team effects varied depending on the strength of team and opposition. Some of these findings will be useful to coaches and performance analysts when planning training sessions and match tactics.